2017
DOI: 10.1186/s12938-017-0325-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the COM-FCP inclination angle and other mediolateral stability indicators for turning

Abstract: BackgroundStudies have shown that turning is associated with more instability than straight walking and instability increases with turning angles. However, the precise relationship of changes in stability with the curvature and step length of turning is not clear. The traditional center of mass (COM)-center of pressure (COP) inclination angle requires the use of force plates. A COM-foot contact point (FCP) inclination angle derived from kinematic data is proposed in this study as a measure of the stability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…Originally the IA method used in this paper was developed as a clinical tool to alleviate the burden of requiring pathologic and elderly subjects to consistently strike the force plate to allow for CoP calculation (Chen and Chou, 2010). Our level surface calculated IAs closely agreed with three (AP HS, ML HS and ML TO) of the four IAs reported originally by Chen and Chou (Chen and Chou, 2010) and with the ML IAs reported by Xu, Wang (Xu, 2017). The difference in the AP TO IAs may be associated with the difference in age of the subjects reported by Chen and Chou (2010) as the average age of the subjects was 77 years compared to 19 years in the current study.…”
Section: Discussionsupporting
confidence: 71%
“…Originally the IA method used in this paper was developed as a clinical tool to alleviate the burden of requiring pathologic and elderly subjects to consistently strike the force plate to allow for CoP calculation (Chen and Chou, 2010). Our level surface calculated IAs closely agreed with three (AP HS, ML HS and ML TO) of the four IAs reported originally by Chen and Chou (Chen and Chou, 2010) and with the ML IAs reported by Xu, Wang (Xu, 2017). The difference in the AP TO IAs may be associated with the difference in age of the subjects reported by Chen and Chou (2010) as the average age of the subjects was 77 years compared to 19 years in the current study.…”
Section: Discussionsupporting
confidence: 71%
“…Walking along curved trajectories requires seamless interlimb coordination, adapted foot placement and fine control of medio-lateral body inclination [ 4 , 9 , 11 , 83 , 84 ]. Here, curved walking significantly decreased walking speed, stride-length and cadence both in HS and in patients with PD.…”
Section: Discussionmentioning
confidence: 99%
“…Curved walking has been studied in terms of muscle activation [ 2 , 3 ], kinematics [ 4 , 3 ] and kinetics [ 3 , 5 ]. These studies have shown modifications in muscle activation, walking speed or kinematics during curvilinear trajectories [ 6 , 7 , 8 , 9 ]. Seemingly, the nervous system orchestrates both straight-ahead and curved walking by modifying the same basic coordination pattern [ 4 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to exploit gravity, the center of foot pressure during heel strike and toe off is being slightly displaced with respect to its position under linear walking. This creates a mediolateral torque that produces and controls trunk roll tilt and progression along the circular trajectory (6, 3335), and generates the proper centripetal force to avoid going off on the tangent (4, 5, 27). Appropriate braking of the body fall toward the interior of the trajectory is exerted by the feet at foot-off (6, 36), such as to counterbalance the reaction forces produced at heel strike (37).…”
Section: Steering the Body Along Curved Pathsmentioning
confidence: 99%